2023
DOI: 10.18006/2023.11(2).297.305
|View full text |Cite
|
Sign up to set email alerts
|

Effect of AM fungi during salt stress on biochemical content in Ginger (Zingiber officinale Rosc.)

Abstract: Ginger (Zingiber officinale Rosc.) is a highly-grown spice crop; its aromatic rhizomes are commercially important due to its high importance in the diet as a spice and some medicinal values. Irrigation methods in India increase salt content in the soil. Arbuscular Mycorrhizal (AM) fungi assist plants under salt stress. However, the vital role of mycorrhizal fungi in ginger salt tolerance has not been evaluated yet and needs to emphasize on its evaluation. The present investigation was conducted to assess the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Results on proline are consistent with those of Liu et al [ 90 ], who reported that AMF inoculation increase proline accumulation in plant tissues via the NO signaling molecule. Indeed, since proline is an amino acid [ 91 ], its biosynthesis is related to the availability of nitrogen, which was more available in inoculated plants. Furthermore, the Mo boosting effect on proline could be attributed to the direct role of Mo on nitrogen metabolism which influenced the proline biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Results on proline are consistent with those of Liu et al [ 90 ], who reported that AMF inoculation increase proline accumulation in plant tissues via the NO signaling molecule. Indeed, since proline is an amino acid [ 91 ], its biosynthesis is related to the availability of nitrogen, which was more available in inoculated plants. Furthermore, the Mo boosting effect on proline could be attributed to the direct role of Mo on nitrogen metabolism which influenced the proline biosynthesis.…”
Section: Discussionmentioning
confidence: 99%